Comparative Chloroplast Genomes of Nicotiana Species (Solanaceae): Insights Into the Genetic Variation, Phylogenetic Relationship, and Polyploid Speciation - Wang, Shuaibin; Gao, Junping; Chao, Haoyu; Li, Zhaowu; Pu, Wenxuan; Wang, Yaofu; Chen, Ming (Frontiers in Plant Science, 2022)
Nicotiana L. is a genus rich in polyploidy, which represents an ideal natural system for investigating the speciation, biodiversity, and phytogeography. Despite a wealth of phylogenetic work on this genus, a robust evolutionary framework with a dated molecular phylogeny for the genus is still lacking. In this study, the 19 complete chloroplast genomes of Nicotiana species were assemblied, and five published chloroplast genome of Nicotiana was retrieved for comparative analyses. The results shown that the 24 chloroplast genomes of Nicotiana, ranging from 155,327 bp (N. paniculata) to 156,142 bp (N. heterantha) in size, exhibited typical quadripartite structure. The chloroplast genomes were rather conserved in genome structure, GC content, RNA editing sites and gene content and order. The higher GC content observed in the IR regions could be a result of the presence of abundant rRNA and tRNA genes, which contained a relatively higher GC content. Total seven hypervariable regions, as new molecular markers for phylogenetic analysis, were uncovered. Based on 78 protein-coding genes, we constructed a well-supported phylogenetic three, which was largely in agreement with previous studies, except a slight conflict on several sections. Chloroplast phylogenetic result indicated that the progenitors of diploid N. sylvestris, N. knightiana, and the common ancestor of N. sylvestris and N. glauca might have donated the maternal genomes of allopolyploid N. tabacum, N. rustica and section Repandae, respectively. Meanwhile, the diploid section Noctiflorae lineages (N. glauca) acted as the most likely maternal progenitor of section Suaveolentes. Molecular dating results shown that the polyploid events range considerably in ~0.12 million (section Nicotiana) to ~5.77 million (section Repandae) years ago. The younger polyploids (N. tabacum and N. rustica) were estimated to have arisen ~0.120 Mya and ~0.186 Mya, respectively. The older polyploids (section Repandae and Suaveolentes) were considered to have originated from a single polyploid event at ~5.77 Mya and ~4.49 Mya, respectively. In summary, the comparative analysis of chloroplast genomes of Nicotiana species have not only revealed a series of new insights to the genetic variation and phylogenetic relationships in Nicotiana but also provided rich genetic resources for speciation and biodiversity research in the future.